Laccase recovery with aqueous two-phase systems: enzyme partitioning and stability - Silvério, Sara C. (2013)
In this work, the potential of several aqueoustwo-phase systems (ATPS) for laccaserecovery was evaluated. For this purpose, different types of ATPS were prepared and the partition coefficient of pure commercial laccase was determined in each one, at 23 °C. A total of 21 ATPS were investigated: 12 composed by a polymer and a salt and 9 composed by two different polymers. For polymer-salt ATPS, different compositions of the same biphasic system were also studied. Laccase partition coefficients (K) obtained were used to conclude about ATPS effectiveness for this enzymerecovery. According to the results, it was found that UCON-phosphate salts (K ≤ 0.604), PEG-Li2SO4 (K = 2.081) and PES-dextran (K = 1.911) ATPS can be interesting options for laccase extraction, with laccasepartitioning towards opposite directions. However, the most effective ATPS for laccase extraction was UCON-K2HPO4, presenting K values from 0.272 up to 0.306. UCON is a thermo-separating polymer which facilitates its recovery and reutilization. Additionally, for the first time, laccasestability in different ATPS was investigated by incubating the enzyme in each equilibrium phase during a week, at room temperature. The results obtained showed that UCON-sulfate salts, UCON-NaH2PO4 and UCON-KH2PO4 ATPS are not recommended for laccaserecovery since a high loss of activity was observed: approximately 88% for sulphates and 80% for both dihydrogen phosphates. The best stability results were obtained with PEG-sulfate salts. For these ATPS, laccasestability remained similar or improved over time.